Key Considerations in Targeted Protein Degradation Drug Discovery and Development - Qin, Liena; Dai, Han; Wang, Junfeng (Frontiers in Chemistry, 2022)
Targeting proteins’ enzymatic functions with small molecule inhibitors, as well as functions of receptor proteins with small molecule agonists and antagonists, were the major forms of small molecule drug development. The small molecule modulators work with conventional occupancy-driven pharmacological approach. For proteome traditionally considered undruggable by small molecule modulators, such as enzymes with scaffolding functions, transcription factors, and proteins lack of well-defined binding pockets, targeted protein degraders offer the opportunity to drug the proteome with an event-driven pharmacological approach. A degrader molecule, either PROTAC or molecular glue, brings the protein of interest (POI) and E3 ubiquitin ligase in close proximity and engages the ubiquitin-proteasome system (UPS), the cellular waste disposal system for the degradation of the POI. For the development of targeted protein degraders to meet therapeutic needs, several aspects will be considered, namely the selective degradation of disease-causing proteins, oral bioavailability of degraders beyond Lipinski’s rule of five (bRo5) scope, demands of new E3 ubiquitin ligases and molecular glue degraders, and drug resistance of the new drug modality. This review will illustrate several under-discussed key considerations in targeted protein degradation drug discovery and development 1) the contributing factors for the selectivity of PROTAC molecules and the design of PROTACs to selectively degrade synergistic pathological proteins; 2) assay development in combination with multi-omics approach for the identification of new E3 ligases and their corresponding ligands, as well as molecular glue degraders; 3) molecular design to improve oral bioavailability of bRo5 PROTACs 4) drug resistance of degraders.